A critical review on biomass-based sustainable biorefineries using nanobiocatalysts: Opportunities, challenges, and future perspectives. (November 2022) - Saratale, Rijuta Ganesh; Cho, Si-Kyung; Bharagava, Ram Naresh; Patel, Anil Kumar; Varjani, Sunita; Mulla, Sikandar I.; Kim, Dong Su; Bhatia, Shashi Kant; Ferreira, Luiz Fernando Romanholo; Shin, Han Seung; Saratale, Ganesh Dattatraya
Graphical abstract: Highlights: Recent research and advances in nano-based enzyme immobilization are discussed. Process employed for creating nanobiocatalyst with greater efficiency, activity, and stability. Co-immobilization strategies to achieve higher catalytic efficiency in cascade reaction. Addressed techno-economic challenges, future perspectives for nano-biocatalyst application. Abstract: Biocatalysts, including live microbial cells/enzymes, have been considered a predominant and advantageous tool for effectively transforming biomass into biofuels and valued biochemicals. However, high production costs, separation, and reusability limit its practical application. Immobilization of single and multi-enzymes by employing different nano-supports have gained massive attention because of its elevated exterior domain and high enzymatic performance. Application of nanobiocatalyst can overcome the drawbacks mainly, stability and reusability, thus reflecting the importance of biomass-based biorefinery to make it profitable and sustainable. This review provides an in-depth, comprehensive analysis of nanobiocatalysts systems concerning nano supports and biocatalytic performance characteristics. Furthermore, the effects of nanobiocatalyst on waste biomass to biofuel and valued bioproducts in the biorefinery approach and their critical assessment are discussed. Lastly, this review elaborates commercialization and market outlooks of the bioconversion process using nanobiocatalyst, followed by different strategies to overcome the limitations and future research directions on nanobiocatalytic-based industrial bioprocesses.